India : Power Sector Reform and the Poor - World Bank (Washington, DC, 2013)
Of all developing countries India has the largest number of poor, as measured by income, health, opportunities and access to basic needs. The national and state governments have carried out a number of initiatives affecting the poor. Of those initiatives, this report focuses on power sector reform efforts, carried out by some Indian states in the mid-1990s. It also aims to answer these questions: What are the main challenges that power reform faces in reducing poverty in India? What are the main obstacles and main opportunities? Are the large subsidies to the power sector reaching the poor? How are the poor affected by the present conditions of power supply and what changes will benefit them most?. In seeking answers to these questions, the report draws on relevant data and studies in India, as well as evidence from the literature and international experience with power sector reform. In view of an ongoing World Bank study on rural electrification that analyzes access issues, and the fact that tariff rebalancing is a major issue, this report focuses on the impact of electricity prices, quality of power supply, access issues, and subsidies to the poor.